2014
DOI: 10.1002/pnp.323
|View full text |Cite
|
Sign up to set email alerts
|

Delirium associated with therapeutic levels of lithium in bipolar disorder

Abstract: Lithium has been associated with neurotoxicity even at ‘therapeutic’ levels. This case report describes a patient with bipolar disorder who developed signs of delirium following an increase in her dose of lithium, even though her serum levels remained in the therapeutic range. Copyright © 2014 John Wiley & Sons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Conversely, the exact mode of action as a mood stabilizing agent is not established (Clough et al 2014 ) but it is reported to interfere with transmembrane sodium exchange in nerve cells by affecting sodium, potassium-stimulated adenosine triphosphatase (Na+, K+-ATPase) stimulus. It has accounted to alter the release of neurotransmitters by affecting cyclic adenosine monophosphate (cAMP) concentrations which blocks inositol metabolism that results in depletion of cellular inositol and inhibition of phospholipase C-mediated signal transduction (Hardman et al 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the exact mode of action as a mood stabilizing agent is not established (Clough et al 2014 ) but it is reported to interfere with transmembrane sodium exchange in nerve cells by affecting sodium, potassium-stimulated adenosine triphosphatase (Na+, K+-ATPase) stimulus. It has accounted to alter the release of neurotransmitters by affecting cyclic adenosine monophosphate (cAMP) concentrations which blocks inositol metabolism that results in depletion of cellular inositol and inhibition of phospholipase C-mediated signal transduction (Hardman et al 2001 ).…”
Section: Introductionmentioning
confidence: 99%